Method of calculating the fuel combustion efficiency in the afterburner combustion chamber of a gas turbine dual fuel engine - A. V. Zhuk; T. V. Grasko; A. S. Kolesnikov; V. V. Raznoschikov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
The problem of reducing the emission of unburned hydrocarbons and carbon monoxide that affect the value of fuel combustion efficiency in the afterburner combustion chamber of a gas turbine engine is considered. An analysis of the causes of hydrocarbon and carbon monoxide formation were carried out and ways to reduce them were identified. The chemical and physical process of the combustion of hydrocarbon fuel with the addition of gaseous hydrogen to its composition is considered with an assessment of the emission of unburned hydrocarbons and carbon monoxide. A method for calculating the fuel combustion efficiency in the afterburner combustion chamber of a gas turbine engine with a dual-fuel power supply system is proposed. It is shown that the application of the developed technique makes it possible to estimate the value of the combustion efficiency and maintain its set value by correcting the percentage ratio of hydrogen to kerosene. The technique was tested during an experimental study of the hydrogen-air mixture combustion in the model compartment of the afterburner combustion chamber of a commercial gas turbine engine.